Hepatoprotective Activity Of Sesamum Indicum Linn. Against Ccl4-Induced Hepatic Damage In Rats - Kumar, Munish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT In present study, the hepatoprotective activity of ethanolic extracts of Sesamum indicum Linn. seeds were evaluated against carbon tetrachloride (CCL4) induced hepatic damage in rats. The extract at two different doses (400mg/kg and 700mg/kg) was administered orally once daily. The substantially elevated serum enzymatic level of Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Glutamate Pyurvate Transaminase (SGPT), alkaline phosphatase (ALP), Acid phosphatase (ACP), Total Protein, Albumin and Total Bilirubin were restored towards normalization significantly by the extract. The biochemical observations were supplemented with histopathological examination of rat liver sections. The results of this study strongly indicate the Sesamum indicum Linn. Seeds have potent hepatoprotective action against carbon tetrachloride induced hepatic damage in rats.